2022
DOI: 10.3390/ijerph192215101
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Feasibility of Remote Assessment of Functioning in Children and Adolescents with Developmental Disabilities: Parents’ Perspectives and Related Contextual Factors

Abstract: The COVID-19 pandemic interrupted face-to-face health services, leveraging telehealth strategies. The aim of this cross-sectional study was to investigate, from a parent’s perspective, the feasibility of a remote assessment of functioning in children with developmental disabilities during the pandemic and related contextual factors, based on how parents carry out the assessment. Parents of children with developmental disabilities (mean age = 7.56 ± 3.68) responded to a remote assessment via electronic forms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…During that time, many more families were in total social distancing; this situation might have impacted all families similarly, which might explain why we did not find an association. Another study from our group showed that the home participation of children with disabilities did not change after 4 months of the pandemic, when most caregivers were practicing partial social distancing 33 during a period when infection rates were high (2020). Therefore, these studies occurred at different stages of the pandemic, with the latter study addressing different samples, thus explaining the contrasting results.…”
Section: Association Of Personal and Environmental Factors With Home ...mentioning
confidence: 96%
“…During that time, many more families were in total social distancing; this situation might have impacted all families similarly, which might explain why we did not find an association. Another study from our group showed that the home participation of children with disabilities did not change after 4 months of the pandemic, when most caregivers were practicing partial social distancing 33 during a period when infection rates were high (2020). Therefore, these studies occurred at different stages of the pandemic, with the latter study addressing different samples, thus explaining the contrasting results.…”
Section: Association Of Personal and Environmental Factors With Home ...mentioning
confidence: 96%